Code Switching in The Calling Novel - Adi, Wiruma Titian; Widyastuti, Tri; Andjani, karina (Center of Language and Cultural Studies [CLCS], 2023)
One of the language phenomena that the writers encounter a lot these days is code switching. Code switching, or a switch from one language to another one while talking, is usually used by the bilingual and multilingual society. The objectives of this research are to find out the types of code switching and the reasons behind them being used by the characters in the novel. The writers use descriptive qualitative information on conducting this research. Books and theories of experts on Sociolinguistics are used as the frame of the study. The source of data is obtained by reading the whole content of the novel, focusing on the utterances and dialogues by the characters. When all is done, the writers finally know that from 4 types of code switching, inter-sentential switching is the most used type. The writers find out that of all reasons, the most common one behind the use of code switching is for the intention of clarifying the speech content for the interlocutor.